(3OjhGf UGdM GdbRhjfjs - (3UGdM Hf egOj Hf QVG Hf eMeO Ydj GdMSjfj GdbRhjfi GdHZOGOjs
(3ChdgG (B:s
(3hHYO(B: (3ajbhd EHQGgje Bd TjN UGOb Ef GdTjN WGdH GdHdGZj GdeMJQe deG cGf eTJedkG Ydi UaGJ hdbO cGf fRQ GdCUWHGQ Ydi GdHCS CWMGQ GdEYSGQ s
(3BNQgG (B:s
(3hdG ZQh, fhQ GdTeS ef ShA aYdge EPG Bd hGdHOQ GdefjQ Edi GdMdc s
(3fSNI KGfjIs
(3LeYgG EHQGgje Bd GdTjN UGOb Bd GdTjN jMji GdYGedjs
(3hHChdgG JQLeI WhjdI ddeDdas
(3hZjQ oeQJH Ydi GdbhGaj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B198 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B13s
Keywords: (3GdCOHs